Analysis by microsatellites (SSR) of genetic diversity in cultivars of Cuban cassava germplasm - Yoel Beovides; Martin Fregene; Alfredo Alves; Janneth P. Gutiérrez; Charles Buitrago; Jaime A. Marin; Marilys D. Milián; Sergio Rodríguez; José A. Cruz; Elianet Ruiz; Dablys Guerra; Humberto Toledo; et al. (Biotecnología Vegetal, 2006)
A study was carried out in order to make a deep analysis of the current knowledges cassava (Manihot esculenta Crantz) genetic diversity, and to evaluate its phylogenetic relationship with relatives cultivated in Africa, and South and Central America in order to facilitate a sustainable management of the genetic resources available in Cuba. A number of 94 cultivars from the Cuban cassava germplasm were studied according to their genetic or economic importance; besides, 54 clones from Africa and America, and 13 genotypes of genetic interest were incorporated. Diversity and genetic differentiation analysis were developed from data of 34 microsatellite markers (SSR). Genetic diversity indexes evidenced the high polymorphism observed for the tested microsatellites. The plant material, coming from Cuba, showed the highest allele average number per locus with 5.8 and as Guatemala, it illustrated 100% polymorphic loci. The highest mean heterozygosity indexes (Ho) are presented by Cuba and Tanzania. The mean rate of heterozygous individuals observed (Ho) was high (0.5918 ±0.0351). These results reported in Cuba for the first time in cassava, offer an important contribution to the genetic breeding program and to the sustainable management of the cassava genetic diversity in Cuba and in the Caribbean area. Key words: genetic differentiation, Manihot, markers, polymorphism, phylogenetic relationship